Inhibitory effects of harlequin glory-bower (Clerodendrum trichotomum) extract on growth of water hyacinth (Eichhornia crassipes) - ZHENG Bin; LU Jian-bo (浙江大学学报. 农业与生命科学版, 2012)
The inhibitory effects of harlequin glory-bower (Clerodendrum trichotomum) water extract on the growth of water hyacinth (Eichhornia crassipes), an invasive aquatic weed which had resulted in enormous ecological and economic consequences in China, were explored and its inhibition mechanism was analyzed by measuring chlorophyll content, catalase activity and malondialdehyde content of water hyacinth leaves. The results showed that the healthy leaf proportion (less than 1%) of water hyacinth which was sprayed the extract was significantly lower than that of the blank group and control group (P<0.01), and the dead leaf proportion (more than 85%) of water hyacinth was significantly higher than theirs (P<0.01), and the chlorophyll content of leaves from treated groups was decreased (P< 0.05), and the catalase activity was enhanced (P<0.05), and the malondialdehyde content was significantly increased (P<0.01). The extract of harlequin glory-bower acted on leaves of water hyacinth, so that the chlorophyll content was decreased, and the reactive oxygen was accumulated to damage biofilm system, resulting in leaves dry rot and decay. In conclusion, the extract of harlequin glory-bower inhibits effectively the growth of water hyacinth, which provids a new biological approach to control water hyacinth.